Drivers of health care expenditure: Does Baumol's cost disease loom large? - Carsten Colombier (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2012)
According to Baumol (1993) health care epitomises Baumol's cost disease. Sectors that suffer from Baumol's cost disease are characterised by slow productivity growth due to a high labour coefficient. As a result, unit costs of these sectors rise inexorably if the respective wages increase with productivity growth of the progressive industries such as manufacturing. Thus, according to Baumol (1993) the secular rise in health-care expenditure has been unavoidable. This present paper demonstrates that health care is contracted by Baumol's cost disease, but only to a minor extent. Consequently, policy-makers have more leeway to curbever-increasing health-care expenditure than is suggested by Baumol (1993) and other authors. In addition, we test the implications of Baumol's cost disease for health care by avoiding the well-known flaws in constructing medical price indices. Therefore, the adjusted Baumol variable derived in this paper is also extremely appropriate to test the validity of Baumol's cost diseases of other service industries such as education or the live performing arts. Additionally, our analysis suggests that health care is rather a necessity than a luxury at the national level, which conflicts with macroeconomic evidence provided in the relevant literature.
Keywords: C23; H51; I10; 330; health-care expenditure; Baumol's cost disease; the macroeconomics of health care; the adjusted Baumol variable